Analisis Faktor Risiko Berhubungan dengan Mortalitas HIV/AIDS di Puskesmas Kencong Jember - Agni Candramawa Sholikha; Maya Weka Santi; Atma Deharja; Ervina Rachmawati (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
AIDS (Acquired Immunodeficiency Syndrome) is a collection of symptoms obtain due to decreased immunity caused by HIV (Human Immunodeficiency Virus). The number of people with HIV/AIDS is increasing, and becoming a global pandemic in the world of child and adult mortality. The highest mortality rate is in Kencong with the number of deaths increasing every year, the highest was in January-July 2019 with 55,88% deaths. The research was aimed to provide an overview of HIV/AIDS mortality in Health Center Kencong, Jember. This research is quantitative descriptive. The samples used were 51 medical record documents of HIV / AIDS patients. The data collection method in this study is a checklist sheet. The data analysis used was univariate analysis. The results showed that most respondents aged 15-49 years were 98.2%, the majority of respondents were male at 67.2%, most respondents had low education <high school (74.5%). It is hoped that the Puskesmas can socialize and provide information to HIV / AIDS patients regarding risk factors for HIV / AIDS mortality so that patients pay more attention to their health.